ثباتية مواصفات دقيق القمح خلال إنتاجه تجارياً - ألفين, فرحان; منصور, دارين (Latakia University Journal -Biological Sciences Series, 2016)
تتأثر خصائص دقيق القمح المنتج بعاملين أساسيين أولهما خصائص حبوب القمح المستخدم والثاني تقنية الطحن المستخدم، أما العوامل الأخرى المؤثرة ومنها عملية تحضير القمح كعملية الترطيب وعملية الطحن، مثل المسافة الفاصلة بين اسطوانات الطحن، كما توجد عوامل أخرى كثيرة. لذلك هدف هذا البحث إلى دراسة التغيرات الحاصلة في بعض المواصفات التكنولوجية (الرطوبة – البروتين – الرماد) واللون والريولوجية (الألفيوغراف والميكسولاب) للدقيق المنتج من مطحنة تجارية خاصة خلال فترة تمتد على شهرين متتالين وذلك لدراسة ثباتية خصائص الدقيق المنتج من نوع واحد من القمح وتقنية طحن ثابتة، والتي تظهر تأثير بعض العوامل العشوائية في عملية الطحن على تغير خصائص الدقيق المنتج في مرحلتين الأولى في خط الإنتاج والثانية في خط التعبئة. تمت دراسة الثباتية من خلال رسم مخططات التحكم الفردية. درست الخصائص الريولوجية لعينات خط التعبئة فقط. نتيجة الدراسة تبين أن تباين الخصائص التكنولوجية لعينات التعبئة أكبر من تباين هذه الخصائص لعينات الإنتاج وخروج عينات عن حدود الضبط مما يعني أن عملية الطحن غير متحكم بها. وأظهرت مخططات التحكم للخصائص الريولوجية لعينات التعبئة خروج عينة واحدة فقط عن حدود الضبط وعلى الرغم من ذلك تبقى ضمن حدود المسموح بها في الطرق القياسية، مما يعني أن عملية الطحن متحكم بها بشكل أفضل بالنسبة للخصائص الريولوجية للدقيق المنتج.The properties of produced flour of wheat are affected by two basic factors: the first is the used wheat properties, the second is the milling technology, and other factors are related to wheat preparation process milling process like the gap between the roller milling and still other random factors. The aim of this research to study the variation of technological properties (moisture content, protein, and ash), color, and rheological properties of produced flour in commercial mill during two month and using a one type wheat and in the same mill, which will show the effects of random factors of the mill process on the variation of produced flour properties at tow point the first at the end of production line and the second at packaging line. Stability of produced flour properties have been determined by using individual control charts. Rheological properties have been studied just for packaging line samples. The variation of technological properties of packaging line sample were greater than production line sample, and laying many sample points out of limiting lines shows that the milling process is out of control. Control charts of rheological properties shows that one sample point out of limiting line, but it still in the range of standard methods repeatability which is mean the process is under control according to packaging line sample rheological properties.